The impact of transcutaneous posterior tibial nerve stimulation in patients with premature ejaculation - Aydos, Mustafa Murat; Nas, İdris; Önen, Efe (The European Research Journal, 2020)
Objectives: Approximately 30-40% of men worldwide are affected by premature ejaculation. Despite much research on this subject, there is still little information about the cause and treatment of premature ejaculation. The aim of this study was to evaluate the therapeutic aspect of transcutaneous posterior tibial nerve stimulation (PTNS) in patients with premature ejaculation.Methods: The study included 60 PE patients, aged 20-50 years, divided into 2 groups as the treatment group (n = 30) and the control group (n = 30). Transcutaneous PTNS was applied to patients in the treatment group for 30 minutes once a week for 12 weeks. In the control group, a stimulation probe was placed on the posterior tibial nerve without giving any stimulation, to provide a placebo effect. The Arabic Index of Premature Ejaculation (AIPE) scale and Intravaginal Ejaculation Latency Time (IELT) measurements were used before and after the procedure.Results: In both groups, the mean IELT duration and AIPE scale scores were statistically significantly increased after the procedure (p < 0.05). The percentage change in the AIPE scale scores after the procedure was found to be higher in the treatment group than in the control group (p = 0.007).Conclusions: The results of the study showed a statistically significant increase in the duration of the time to ejaculation with PTNS, and a significant improvement was obtained in the post-treatment AIPE scale scores. There is a need for further research to achieve more robust results to contribute to premature ejaculation treatment.